THE DEVELOPMENT OF AN AUTONOMOUS, ENERGY-EFFICIENT PEDESTRIAN CROSSING LIGHTING COMPLEX - ДЗІКЕВИЧ, А. В.; ІВАНОВА, М. С.; ОЛЕЙНІКОВА, І. В. (Technologies and Engineering, 2023)
Purpose. Justification and design of a self-contained complex for a pedestrian crossing with increased energy efficiency. Introduction of alternative energy sources with appropriate design. Application of fluorescent and phosphor coatings to create a single autonomous and safe system. Use of specialised spectrum light sources as a method of enhancing the functionality of the built complex. Methodology. The comprehensive approach, which combines specific radiation sources with unique pavement elements to create a safe pedestrian zone. Innovative introduction of modern alternative energy sources in areas with higher power demand, significantly increasing energy efficiency. Modern computer software tools with 3D modeling offer unlimited possibilities for the design of a model autonomous lighting complex. Above all, the initiative aims to create a safe environment for pedestrians in the high-crash area due to the significant damage to the country's energy infrastructure. Findings. The comprehensive work on the system has significantly reduced the hazardous areas created by the critical mass energy supply situation. The project is not limited to solving functional problems, but also offers a unique design solution. The complex is far superior to other designs available, as it provides a self-contained system, including a power supply. The combination of ultraviolet light and phosphor coating is an innovative technical solution and aesthetically harmonious in terms of design. Originality. This project integrates a variety of technologies previously used as standalone solutions. For the first time, many technical components are combined to illuminate a pedestrian crossing through a single interconnected complex. The advantage is that the system is energy-independent, which is essential in today's world. The characteristic design, based on the technology used, blends in well with all the components of the complex. The installation of reflective coverings will create additional lighting accents and draw the attention of vehicles to the pedestrian crossing. Practical value. Due to inadequate lighting associated with frequent blackouts, there are now many accidents on the roads. Through the synthesis of many technologies and the development of a self-sustaining system, the complex will be able to contribute to a partial solution to the current problem. The mass installation of this lighting complex on city streets will achieve the desired illumination and create a safe space for pedestrians. The benefits of the lighting system's design are its stability and the ergonomics of the structure itself. The UV light sources will not only create the light itself but will also serve as a feed for the solar panels. The efficient design of the placement of the solar panels themselves will ensure that natural light is always fully accessible. The proposed use of self-luminous elements in the work, namely fluorescent and luminofor paint, will create an additional lighting solution that will improve visibility for pedestrians and drivers, as well as being a visually appealing addition to the complex itself.